Sustainable food consumption in China and India - Marie von Meyer-Höfer; Andrea Maria Juarez Tijerino; Achim Spiller (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2015)
This study examines sustainable food consumption in China and India, based on online consumer survey data. It explores which factors influence sustainable food consumption in these countries, based upon a model related to the Theory of Planned Behaviour. Structural equation modelling is used for the analysis and comparison of both countries. Among the similarities found are the significant influence of subjective norms on intention towards sustainable food consumption and the influence of perceived consumer effectiveness on sustainable food consumption behaviour. Price is identified as a barrier to sustainable food consumption. Based on these findings policy and marketing implications are given.
Keywords: Q13; Q18; Q19; 330; sustainable food consumption; consumer behaviour; partial least squares; China; India